CHARACTERISTICS OF RADIOLUCENT LESIONS ASSOCIATED WITH IMPACTED TEETH AT RSGM UNPAD - Jihan Nahdatul Putri; Indra Hadikrishna; Yurika Ambar Lita (FKG ULM, 2024)
Background: Impacted teeth occur when teeth fail to erupt or cannot fully erupt along the dental arch in the normal pattern of dental growth. Untreated impacted teeth can cause pain, tooth decay, inflammatory lesions, odontogenic cysts, and tumors. Pathological lesions in impacted teeth that are not clinically visible are usually found on routine radiographic examinations. Panoramic radiography is used as an initial imaging technique to evaluate impacted teeth and associated lesions. Purpose: This study aims to see the characteristics of radiolucent lesions associated with impacted teeth based on panoramic radiographic archives of patients at RSGM Unpad. Methods: This is an observational descriptive study with purposive sampling technique using secondary data of panoramic radiographs from the Dental Radiology Installation RSGM Unpad. The radiographs were inverted to enhance the visualization of characteristics such as location, shape, borders and associations. The data is presented in the table of frequency and distribution. Results: 346 samples of radiolucent lesions associated with impacted teeth were obtained from 8034 impacted teeth. There were 323 (93,4%) pericoronal lesions, 344 (99,4%) monolocular lesions, 218 (63%) had well-defined borders, and 345 (99,7%) lesions caused bone destruction. The prevalence of radiolucent lesions associated with impacted teeth is 4.3%. Conclusion: The characteristics of radiolucent lesions associated with impacted teeth at the Dental Radiology Installation RSGM Unpad most common are pericoronal lesions, monolocular shape, well-defined borders, and the effect on the surrounding structure is bone destruction.Impacted, Panoramic Radiograph, Radiolucent Lesion